The role of senior management in natural hazards: a European banking industry case - Somogyi, Tamas; Nagy, Rudolf (Serbian Journal of Management, 2025)
The issue of natural hazards is a major area of interest within the field of security and business management. Proper risk management has been found to be fundamental, thus has received considerable attention. However, very little attention has been paid to the role of senior management within an enterprise’s risk management framework. This paper seeks to explore this special role in the risk management process, especially when dealing with the risks related to natural hazards. The appropriate role of senior management in managing the risks related to natural hazards is a key issue. The European banking industry’s approach is presented, based on the publicly available sector-specific regulations and guidance. Some recommendations are provided to further enhance the key role of senior management in natural hazards. Our result is considered as a solution that can be adopted by enterprises, organisations and institutions in any sector
Keywords: senior management; risk management; natural hazards; banking industry